Effects of the Equivalent Geometric Nodal Imperfections on the stability of single layer grid shells. (1st April 2016) - Bruno, Luca; Sassone, Mario; Venuti, Fiammetta
Highlights: Effects of imperfections on the stability of a single layer hybrid grid shell. Imperfection field defined through Eigenmode Imperfection Method. Parametric numerical simulations with different structural models. Load factor and deformed shape at collapse are highly sensitive to imperfection. Failure mode related to a local metric of the grid shell geometry, named nodal apex. Abstract: The present paper discusses the sensitivity of the global and local stability of a hybrid single layer grid shell to a set of Equivalent Geometric Nodal Imperfections representative of the actual structural and construction imperfections. Since imperfections are hard to be measured and controlled in experimental facilities, the stability of the structure is extensively investigated in numerical experiments. The imperfections are set by means of the so-called Eigenmode Imperfection Method. The method parameter space is densely sampled, and different structural models are adopted. The results are given in terms of two bulk parameters: the well established Load Factor and the proposed Buckling Shape Length, the latter being introduced to provide a continuous measure of the degree of "globalness" of the instability. Significant and non monotonic changes in both the Load Factor and Buckling Shape Length are observed versus the growth of the imperfection amplitude. Further, a local metrics of the grid shell geometry, named nodal apex, is introduced for each structural node. Special emphasis is given to the analysis of the correlation between the apex of the initial imperfect geometry and the apex of the deformed shape at collapse. The observed high correlation suggests that the mechanical behavior of the imperfect grid shell is significantly influenced by this local geometrical feature.